(untitled) (Journal of Contemporary Philology, 2019)
This article explores and aims to identify and foreground the dystopian aspects of Kazuo Ishiguro’s novel Never Let Me Go in the context of identity, memory and lack of resistance. Various issues have been raised in previous research in regard to this novel, such as: how the narrator’s memory is related to her identity, why don’t the clones show any sign of opposition to the situation they are in, does the ending provide an optimistic view of the world. The utopian elements of Never Let Me Go, however, have not been much discussed. The objective here is to place Ishiguro’s novel in the context of the utopian tradition, since such an approach will provide new perceptions about the above-mentioned questions. The research will show how the novel’s dystopian elements are helpful in understanding the nature of the clones, their identity and memory.